Atmospheric Rivers Carry Nonmonsoon Extreme Precipitation Into Nepal. Issue 11 (12th June 2018) - Thapa, Kritika; Endreny, Theodore A.; Ferguson, Craig R.
Abstract: Atmospheric rivers (ARs) are concentrated bands of water vapor that can cause extreme precipitation and severe flooding. Fortunately, due to their 1, 500+ km spatial extent, they may also be forecasted days in advance. The goals of this study were to investigate the seasonal climatology of ARs in the Himalayan region of Nepal and to determine the role of ARs in extreme precipitation events. Using the ERA‐Interim atmospheric reanalysis, we applied a standard integrated vapor transport AR detection approach for the 35‐year period from 1979 to 2013. We detected 433 ARs, or approximately 12 ARs yearly. Along our six (0.75°) grid detection transect, ARs explain 35% of grid annual maximum daily precipitation events and 70% of grid nonmonsoon (October–May) maximum daily precipitation events. In 89% and 71% of years, at least one of the six detection grids experienced an AR‐related nonmonsoon maximum or annual maximum event, respectively. Overall, ARs explain 78% of daily precipitation totals exceeding 33 mm in the nonmonsoon season in comparison to 18% if the entire year is considered. As we show, ARs constitute a valuable new lens through which extreme precipitation in the region may be understood and forecasted. However, follow‐on integrated vapor transport analyses that more closely investigate the interaction between ARs and their synoptic‐scale environment are needed to better differentiate January and February ARs from Western Disturbances and June–September ARs from the Indian monsoon. Key Points: Atmospheric rivers (ARs) are a dominant source of extreme precipitation in Nepal during the nonmonsoon period ARs explain 35% of annual maximum daily precipitation events, 70% if considering only the nonmonsoon period